English grammar in use - Murphy, Raymond (Cambridge University Press, 2012)
Book accompanied by CD-ROM: English grammar in use CD-ROM. Version 1.0 : hundreds of additional exercises to accompany the third edition of the book ; and booklet: English grammar in use CD-ROM user's guide / Miles Craven and Brigit Viney; Includes index